Resting-state fMRI activation is associated with parent-reported phenotypic features of autism in early adolescence - Hickson, Robert; Hebron, Liberty; Muller-Oehring, Eva M.; Cheu, Anastasia; Hernandez, Andres; Kiss, Orsolya; Gombert-Labedens, Marie; Baker, Fiona C.; Schulte, Tilman (Frontiers in Child and Adolescent Psychiatry, 2024)
Autism Spectrum Disorder (ASD) is characterized by deficits in social cognition, self-referential processing, and restricted repetitive behaviors. Despite the established clinical symptoms and neurofunctional alterations in ASD, definitive biomarkers for ASD features during neurodevelopment remain unknown. In this study, we aimed to explore if activation in brain regions of the default mode network (DMN), specifically the medial prefrontal cortex (MPC), posterior cingulate cortex (PCC), superior temporal sulcus (STS), inferior frontal gyrus (IFG), angular gyrus (AG), and the temporoparietal junction (TPJ), during resting-state functional magnetic resonance imaging (rs-fMRI) is associated with possible phenotypic features of autism (PPFA) in a large, diverse youth cohort. We used cross-sectional parent-reported PPFA data and youth rs-fMRI brain data as part of the two-year follow-up of the Adolescent Brain Cognitive Development (ABCD) study. Our sample consisted of 7,106 (53% male) adolescents aged 10-13.We conducted confirmatory factor analyses (CFAs) to establish the viability of our latent measurements: features of autism and regional brain activation. Structural regression analyses were used to investigate the associations between the six brain regions and the PPFA. We found that activation in the MPC (β = .16, p < .05) and the STS (β = .08, p < .05), and being male (β = .13, p < .05), was positively associated with PPFA. In contrast, activation in the IFG (β = -.08, p < .05) was negatively associated. Our findings suggest that regions of the "social brain" are associated with PPFA during early adolescence. Future research should characterize the developmental trajectory of social brain regions in relation to features of ASD, specifically brain regions known to mature relatively later during development.